Tactile Cartography and School Geography: Methodological propositions for learning time zones - Santos, Jadson (2021)
This writing is within the scope of the extension action entitled Teaching Practices in School Cartography (UNEB / Campus IV), which fostered the construction of pedagogical practices that enhance teaching-learning through the mediation of cartographic language. In the meantime, we have developed, based on the inclusion in the teaching of Geography, through Tactile Cartography, the proposition of building tactile maps for blind and low vision students, with a view to apprehending the concept of time zone. Therefore, the objective of this work is to analyze the potential of tactile maps in the construction of geographical reasoning for blind and low vision students, through the abstraction of the concept of time zones and; for this, we traced a methodological path anchored in qualitative research, bearing in mind the proximity of researchers with the object in question. Therefore, we highlight the need to think about the construction of tactile maps in the context of the classroom to assist in the reading of geographic space, in the understanding of its forms and limits, in the analysis of territorial contours, but also, in the case of the concept in question, enabling a better perception of imaginary lines, the dimension of time zones and how these influence our daily lives.